1998
DOI: 10.1055/s-1998-1763
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Stereoinduction in Radical Additions to Glyoxylate Imines

Abstract: Addition of alkyl radicals to the acyclic glyoxylate imine 1 proceeded with a 70 : 30 stereoinduction, even at -78 °C. Addition to the cyclic imine 4b resulted in complete stereocontrol at -40 °C.If one excepts spin-trapping techniques using nitrones, 1 the field of radical addition to C=N bonds 2 has expanded slowly compared to that of radical addition to C=C bonds. Among the various classes of nitrogen containing radical acceptors, imines have received much less attention than for instance oxime-ethers or hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 3 publications
(4 reference statements)
0
40
0
1
Order By: Relevance
“…By using a triethylborane as a chain transfer reagent, the reaction could be extended to alkyl iodides as radical precursors. Bertrand [94,114] and Naito [95,97] reported both the use of triethylborane for the tin-free addition of alkyl iodides to imines. A typical example for a tentative of asymmetric addition to a glyoxylate imine is depicted in Scheme 50 (Eq.…”
Section: Via Iodine Atom Transfermentioning
confidence: 99%
“…By using a triethylborane as a chain transfer reagent, the reaction could be extended to alkyl iodides as radical precursors. Bertrand [94,114] and Naito [95,97] reported both the use of triethylborane for the tin-free addition of alkyl iodides to imines. A typical example for a tentative of asymmetric addition to a glyoxylate imine is depicted in Scheme 50 (Eq.…”
Section: Via Iodine Atom Transfermentioning
confidence: 99%
“…Bertrand et al reported diastereoselective radical addition to glyoxylate imines 33 [26]. Compared with the "Bu3SnH/AlBN system, stereoselectivity of the products is higher when EtjB and no "BulSnH were employed at -40°C (Scheme 19).…”
Section: Lewis Acidic Triaikyiborane: Radical Mediator and Terminatormentioning
confidence: 99%
“…3 We have reported recently that triethylborane could promote the radical reaction between alkyl iodides and glyoxylic imines in a procedure which avoids completely the use of any tin derivative. 4 Concomitantly the group of Naito has investigated Et 3 B mediated intermolecular additions onto oxime ethers. 3g-j It must be underlined that contrary to our observations on imines, these reactions could not be performed in the absence of tributyltin hydride except for the addition of ethyl radical.…”
mentioning
confidence: 99%